Paleointensity studies on Holocene–Pleistocene sediments from lake Escondido, Argentina - Gogorza, Claudia Susana (2004)
Relative changes in geomagnetic field intensity over the last 16,000 years BP were recovered from the study of four cores obtained from Lake Escondido (South Argentina). Rock magnetic analysis shows that the main magnetic mineral is magnetite, the concentrations being mainly between 0.01 and 0.1%, and the grain size between 1 and 8_m. In order to fulfil the criteria for assessing the reliability of paleointensity data derived from sediments [Rev. Geophys. 31 (1993) 319], the samples whose concentrations and size are beyond this range were rejected. The remanent magnetisation at 20mT(NRM20mT)was normalised using the anhysteric remanent magnetisation (ARM100mT), the saturation of the isothermal remanent magnetisation (SIRM) and the low field magnetic susceptibility (k). Coherence function analysis indicates that the records are not significantly affected by local environmental conditions. This suggests that the variations in normalised remanence are mostly likely due to geomagnetic paleointensity fluctuations. ARM100mT is the best normaliser for the Lake Escondido sediments. The record of relative paleointensity (NRM20mT/ARM100mT) shows peaks and troughs whose amplitudes are similar to those in the St. Lawrence Estuary, Lake Baikal, Lake Pepin and Larsen-A Ice shelf data set and a stack of archeomagnetic data given as virtual axial dipole moment (VADM).